COMMON TYPES OF MENTAL DISORDERS IN ADULT CANCER PATIENTS SEEN AT SHAUKAT KHANUM MEMORIAL CANCER HOSPITAL AND RESEARCH CENTRE - Iqbal, Akhtar (Journal of Ayub Medical College Abbottabad, 2004)
Background: Mental disorders such as depression, anxiety and adjustment disorders occur in a significant number of cancer patients, particularly as disease advances and as cancer therapies become more aggressive. Methods: 365 newly diagnosed adult cancer patients were interviewed by clinical psychologist and data was collected regarding patients' age, gender, education, home atmosphere, family support system and type of cancer. The Mini Mental State Examination (MMSE) and Structured Clinical Interview according to Diagnostic and Statistical Manual fourth version (SCID-IV) were used to record the presence and absence of type of a mental disorder. Data thus collected was analyzed by utilizing SPSS for Windows version 10.0. Results: Adjustment disorders was the most common type of mental disorders seen in 20.8%; depression in 17.8% and anxiety in 16.8%. A statistically significant association between types of mental disorders and patients' age, gender, education, home atmosphere and family support system was observed. Conclusion: A significant number of cancer patients suffer from one or other type of mental disorder. They need special attention of healthcare professionals for proper psychological assessment and management. Key Words: Mental Disorders; Cancer; Family Support; Anxiety; Depression